Determination of the Specific Surface Areas of Non-Porous and Macroporous Carbons - J. Choma; M. Jaroniec (Adsorption Science & Technology)
The current work is focused on the examination of a new method for the determination of the specific surface areas of non-porous and macroporous carbons from gas adsorption isotherms. This method has rigorous foundations since it utilizes the adsorption potential distribution which is a unique thermodynamic characteristic for a given adsorption system. Nitrogen adsorption isotherms at 77 K for a series of low-surface area graphitized and non-graphitized carbons were used to examine this method and to compare it with the BET procedure. Additional testing was undertaken for argon, nitrogen and krypton adsorption isotherms at 87 K on a highly graphitized carbon. It was shown that surface area analysis based on the adsorption potential distribution is very promising for the characterization of various carbons.